2018
DOI: 10.1136/bmjopen-2017-021244
|View full text |Cite
|
Sign up to set email alerts
|

Trends in asthma hospital admissions and mortality in Kuwait, 2000–2014: a national retrospective observational study

Abstract: ObjectivesTo examine trends in asthma hospitalisation and mortality rates from 2000 to 2014 in Kuwait according to sex, age and nationality.MethodsFor this nationwide, retrospective observational study, data from hospital discharge records and death certificates listing asthma as the primary reason for hospitalisation or mortality were obtained from the National Center for Health Information database using International Classification of Diseases, Tenth Revision codes J45 and J46. Trends in sex-adjusted, age-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…One of the main results of the present study is that for patients 0–15 years old, the hospitalization rate for asthma in Mexico (2010–2018) was higher in males, but it was higher in females for the other age groups. These results are similar to studies carried out in Kuwait by Ziyab et al and Santos et al carried out in Portugal [ 29 , 35 ]. However, in a study carried out in Mexico City by Del-Rio-Navarro and colleagues, the difference in the prevalence of the disease by gender is not significant in children and adolescents in the general population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One of the main results of the present study is that for patients 0–15 years old, the hospitalization rate for asthma in Mexico (2010–2018) was higher in males, but it was higher in females for the other age groups. These results are similar to studies carried out in Kuwait by Ziyab et al and Santos et al carried out in Portugal [ 29 , 35 ]. However, in a study carried out in Mexico City by Del-Rio-Navarro and colleagues, the difference in the prevalence of the disease by gender is not significant in children and adolescents in the general population.…”
Section: Discussionsupporting
confidence: 92%
“…Among hospitalized patients, epidemiological characteristics are related to clinical courses and outcomes among patients. Consistent with previous studies in the USA, Brazil, France, Kuwait, Costa Rica, and Galicia, we found a reduced asthma hospitalization rate for all age groups throughout the studied period [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Vargas et al reported a similar decreased health services trend of asthma over the years translating, into a decrease in hospitalizations [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…The Global Burden of Diseases study estimated that, in 2017, more than 272 million people were living with asthma and it accounted for over 10.6 million years lived with disability [2]. Incidence and prevalence rates are highest in children, but asthma-related morbidity, healthcare use and mortality are higher in adults [4,5]. Although in comparison with other chronic diseases mortality related to asthma is relatively low, in 2016 poorly controlled asthma was responsible for approximately 400 000 deaths worldwide [3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies estimate that approximately 10-12% of adults in Kuwait are asthmatic, compared to only 4-8% in Turkey, Egypt, UAE and Saudi Arabia [6]. [[,7] Despite the increasing prevalence of asthma worldwide, improvement in management strategies and treatments and access to high quality healthcare services in Kuwait have led to substantial reductions in asthma-related hospital admission and mortality rates in this country [4,5]. Nevertheless, chronic asthma in this country is associated with significant comorbidity and impaired quality of life, and management and treatments are associated with considerable financial burden [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In Iraq, about 200,000 patients per year with asthma are either hospitalised or treated in an emergency room. Prevalence of asthma in the adjacent countries to Iraq includes 5.6 % in Saudi Arabia and 8.5 % in Kuwait [4], [5].…”
Section: Introductionmentioning
confidence: 99%